Factors Influencing Madrasah E-Learning Satisfaction on Mathematics Teachers of Madrasah Tsanawiyah in Jakarta - Merrydian, Siska; Yumiati, Yumiati; Noviyanti, Mery (Universitas Muhammadiyah Mataram, 2022)
This study analyzes the effect of attitude, quality, and flexibility on satisfaction and the implications for the desire to continue using madrasah e-learning for mathematics teachers in seventh grade for algebra material. The research includes non-experimental quantitative research. The population of this research is a mathematics teacher at the seventh-grade Madrasah Tsanawiyah in DKI Jakarta Province who teaches algebra material using madrasah e-learning. Sampling by convenience sampling and obtaining a sample of 225 teachers. The method of data collection is using a questionnaire. A Likert scale 1-5 questionnaire to collect data, data analysis method using PLS-SEM. Interviews with nine teachers were conducted to explore the causes of teachers agreeing and disagreeing with using e-learning madrasah in algebra learning. The results showed that teacher attitudes, e-learning quality, and e-learning flexibility significantly and positively affected e-learning satisfaction. E-learning satisfaction significantly and positively affects the desire to continue using e-learning. The interviews showed that teachers agreed because e-learning madrasah could help and facilitate teachers and students, and teachers did not agree because they encountered some difficulties in learning algebra.